KESENJANGAN GENDER PADA LEMBAGA PENYELENGGARA PEMILU PROVINSI JAWA TENGAH - Hafifah Bella Nugraheni; Nur Hidayat - Sardini; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2023)
The presence and representation of women in public and political spheres is still not visible to this day. Women have the right to participate, the right to vote, and the right to be elected and even have a legal umbrella that encourages their representation in election management institution. The background of this research is the low participation of women in the Central Java Province Election Institution in this day, even though they have been given encouragement through affirmative ideas to the applicable legal framework. This research aims to explain the description of the women existence in Central Java Province election management institution. In addition, this research also explain the inhibiting and driving factors for the women existence in the Central Java Province election management institution. In this research, efforts to answer the problems and research objectives are carried out using the theory of women's representation in the public sphere, affirmative action through Law Number 7 of 2017 about Elections, and the political recruitment system. The subjects in this research are the Central Java Province Election Organizing Institution consisting of the Central Java Province KPU and the Central Java Province Bawaslu in the process of recruiting prospective members for the 2018-2023 Central Java Provincial Election. Through a qualitative method with a descriptive approach, this research will answer several problems and analysis related to the low existence of female members in the Central Java Province election management institution for 2018 – 2023. The results of this research indicate that there is an affirmation idea that is applied in the recruitment stage even though it is not yet optimal in its application. In addition, cultural, intra-personal, and structural-formal barriers were found in the initial process of recruiting prospective members for women